Kreative erhverv i Norden - Nordic Council of Ministers (TemaNord, 2015)
Architecture; Computer games; Design; Film and TV; Journalism; Art and Culture; Literature; Media; Music; Museums and cultural heritage; Performing arts; Visual arts; Business; Creative industries; Information Technology